Omega-3 fatty acid regulation of lipoprotein lipase and FAT/CD36 and its impact on white adipose tissue lipid uptake - Patrick V. McTavish; David M. Mutch (Lipids in Health and Disease)
Abstract Lipid uptake by white adipose tissue (WAT) is critically important for storage of excess energy and to protect peripheral tissues from ectopic lipid deposition. When WAT becomes dysfunctional (i.e., with obesity), it is characterized by impaired lipid uptake and increased lipolysis which, together, promote whole-body dyslipidemia. Omega-3 polyunsaturated fatty acids (N-3 PUFA) are widely studied for their triacylglycerol (TAG)-lowering properties and cardiometabolic health benefits. One potential mechanism underlying these benefits is the modification of WAT lipid uptake; however, there are gaps in our understanding regarding the specific mechanisms by which N-3 PUFA function. Evidence to date suggests that N-3 PUFA promote TAG clearance by increasing lipoprotein lipase (LPL) activity and the abundance of fatty acid transporters. Specifically, N-3 PUFA have been shown to increase LPL activity through increased gene transcription and modifications of endogenously produced LPL regulators such as apolipoprotein C-II/III and angiopoietin-like proteins. This review presents and discusses the available in vitro and in vivo research to provide a comprehensive overview of N-3 PUFA regulation of WAT lipid uptake in healthy and obese contexts. Additionally, we highlight areas where more research is necessary to better understand the contribution of increased WAT lipid uptake in relation to the TAG-lowering properties associated with N-3 PUFA.